Histopathological Spectrum of Adult and Paediatric Meningiomas - Pant, Ishita; Chaturvedi, Sujata; Sarma, Pragyan; Sehgal, Shelly (Annals of Pathology and Laboratory Medicine, 2022)
Introduction: Meningiomas are a group of neoplasms showing a spectrum of histopathological variants, mostly corresponding to World Health Organization (WHO) grade I. However, certain histologic variants correspond histologically to WHO grades II and III. In this study, the histopathological spectrum of the adult as well as paediatric meningiomas received in our department over the last 12 years is being revisited with the aim to analyse the various histopathological variants, to assess their grade as per WHO 2016 criteria, their epidemiology and localization. Material and methods: A retrospective analysis of the histopathology records and clinical case files was done in 336 cases of (adult and paediatric meningiomas) histopathologically diagnosed cases of intracranial and intraspinal meningiomas (WHO grade I, II and III) received over a period of 12 years (starting from 2009-2020) in our department. Results: The commonest grade in adults and children was WHO Grade I while the commonest histopathological variant in adults and children was Transitional meningioma. Conclusion: As per WHO classification of CNS Tumours 2016, grade I meningiomas are associated with low risk of recurrence and aggressive behaviour, while WHO grade II and III meningiomas are associated with greater likelihood of recurrence and aggressive behaviour, highlighting the importance of accurate typing and grading of meningiomas on histopathology.